Stability for grain oil content in sorghum (Sorghum bicolor) - RAKSHIT, SUJAY; C, ARUNA; YADAV, PRADUMAN; PATROTI, PARASHURAM; GIRISH, G; N, GANAPATHY K; V, RATNAVATHI C; G, PADMAJA P; M, BAHADURE D (The Indian Journal of Agricultural Sciences, 2021)
Oil content in sorghum [Sorghum bicolor (L.) Moench] grains is an important component in determining sorghum as a functional food. Sorghum has unique advantage in terms of its high tolerance to drought and high temperatures. With its ability to yield high with low inputs, it can be used as an alternative oil source with clinical advantages. Breeding efforts towards identifying end use of specific cultivars are required for increased profitability to the farmers. In the present study, oil content was estimated in 19 genotypes over three locations (Gulberga, Solapur and Hyderabad) which were sown in randomized block design with three replications during post rainy season of 2016-17. Oil content ranged from 3.14–4.76% with the highest value in IS 30466. Germplasm lines, IS 31681, IS 1212, IS 30536, IS 30507, IS 603 and IS 30466 were found better adapted to all test environments with stable mean oil content more than population mean. Significant effects of both genotype and environment were observed for oil content, while genotype × environment interaction was not significant indicating that the genotypes do not show differential response to the environment. Oil content had significant correlation with germ size (r = 0.484), while the associations with 100-seed weight and grain hardness were non-significant. The information generated and the genotypes identified will help in breeding sorghum with high oil content thus enhancing the demand for sorghum as an industrial crop.